Solar dryer: Laboratory experiment and initial evaluation of the solar-dried tomatoes and peppers - Salaudeen, Kamaldeen Oladimeji; Yamauchi, Futoshi; Liu, Yanyan (International Food Policy Research Institute, 2024)
Nigeria’s Kano State is a major vegetable growing area. Commonly grown vegetables are tomatoes, peppers, onions, carrots, and leafy greens. These vegetables suffer from high post-harvest loss. Smallholder farmers, market and aggregators, actors rely on traditional drying practices such as sun drying during glutting seasons. The dried vegetable market is fast growing. It has been reported that drying vegetables increases the shelf life and favors year-round availability or supply of a vegetable crop to the market. However, these traditional practices are inefficient and unreliable for food safety. Rethinking Food Market and Plant Health Initiatives of CGIAR aim to introduce an energy-efficient, low-cost, and hygienic technology, that is, a solar drying system with support from the Nigeria Stored Product Research Institute’s (NSPRI) to dry vegetable crops in smallholder farmers communities in Kano State. In addition to being relatively faster drying process, the use of a solar dryer provides a more controlled and consistent drying environment, thereby protecting the produce from exposure to dust, insects, and other contaminants, and microbial growth. The controlled environment also helps maintain product quality, nutritional value, and appearance of dried products. As a result, solar drying processes produce good quality products and can be sold at a better price on the market (Aravindh and Sreekumar 2015). The aim of this study is to ascertain the effect of the solar dryer on qualities and safety of the dried tomatoes and peppers.